APLIKASI PROGRAM ARC - SDM PADA PENGINDERAAN JAUH UNTUK PEMETAAN MINERAL EMAS - CENI FEBI KURNIA SARI (Universitas Negeri Padang, 2020)
The application of the Arc SDM program on remote sensing for gold minerals ini an area can be implemented by proving the compatibility of the result of the interpretation of satellite image with conditions in the study area. Remote sensing method is able to detect potential locations with mineral deposits occurrence that has certain characteristics that can affect a certain aspect of exploration activities, namely time efficiency. Remote sensing is an art and technique for obtaining information on an object, area or data analysis phenomenon acquired with a device without having to have direct contact with the object, area or phenomenon studied. In remote sensing, exploration activities play an important role in terms of isolating the potential of seed sediment based on remote sensing models. The use of remote sensing method can reduce exploration costs because it only focuses on detailed surface area of research that have more potential for the existence of minerals. By using this remote sensing method, we can determine specific area to explore, researching in detail in the shortest time possible. Mapping method for the mineralization geological exploration activities in the intended gold-bearing areas can utilize remote sensing data in the form of Landsat ETM satellite images. This method is expected to be able to produce accurate, valid and up-to-date data that makes it possible to create geological interpretation maps in a relatively short time (Rapid Mapping).